Machine learning and AI techniques in interactive medical image analysis - Panigrahi, Lipismita 1989-; Biswal, Sandeep 1987-; Bhoi, Akash Kumar; Kalam, Akhtar; Barsocchi, Paolo (Advances in medical technologies and clinical practice (AMTCP) book series, 2023)
The healthcare industry is predominantly moving towards affordable, accessible, and quality health care and this book investigates how organizations are striving hard to build communication compatibility among the wide range of devices that have operated independently and therefore boosting the research in the medical imaging field.